2022
DOI: 10.1007/s00432-022-04271-z
|View full text |Cite
|
Sign up to set email alerts
|

High RIG-I and EFTUD2 expression predicts poor survival in endometrial cancer

Abstract: Purpose Endometrial cancer is the most common gynecological malignancy. The helicase RIG-I, a part of the innate immune system, and EFTUD2, a splicing factor which can upregulate RIG-I expression, are shown to influence tumor growth and disease progression in several malignancies. For endometrial cancer, an immunogenic cancer, data about RIG-I and EFTUD2 are still missing. The aim of this study was to examine the expression of RIG-I and EFTUD2 in endometrial cancer. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, the role of RIG-I in cancer is not without controversy. RIG-I expression is downregulated and correlates with prolonged survival in HCC, but high RIG-I expression predicts poor clinical outcome for endometrial cancer [ 41 , 42 ]. Here, we show circKEAP1 triggers an immune defense response by binding to RIG-I in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of RIG-I in cancer is not without controversy. RIG-I expression is downregulated and correlates with prolonged survival in HCC, but high RIG-I expression predicts poor clinical outcome for endometrial cancer [ 41 , 42 ]. Here, we show circKEAP1 triggers an immune defense response by binding to RIG-I in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is an element of high novelty since the role of EFTUD2 has been underestimated in the field of cancer research in comparison to others small nuclear ribonucleoprotein such as U2AF1 and SF3B1. Indeed, up to now, only four papers have been published describing the involvement of EFTUD2 in the colitis-associated tumorigenesis [ 30 ], in the endometrial cancer [ 31 ] and in the HCC [ 32 , 33 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ESCC cell migration and invasion can lead to metastasis [ 1 , 3 ]. RIG-I plays an important regulatory role in the development of a variety of tumors [ 20 , 21 , 22 , 23 , 24 , 26 ]; its expression is upregulated in ovarian [ 22 ], colorectal [ 23 ], and endometrial cancers [ 24 ]. This study, for the first time, confirmed the carcinogenic effect of RIG-I in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the regulatory role in tumors has been demonstrated, the low expression of RIG-I in melanoma and colon cancer is associated with a poor prognosis [ 20 , 21 ]. RIG-I is overexpressed in ovarian, colorectal, and endometrial cancers; it plays an essential role in proliferation, apoptosis, and immune escape [ 22 , 23 , 24 ]. Therefore, RIG-I is a potential target for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%